Gold and Antimony Mineralizations of Jbel Haouanite (High Atlas, Morocco) in Their Geodynamic Context - Addi, Azza; Abdellah, Boushaba; Ali, Moukadiri (European Scientific Journal, ESJ, 2019)
The gold and antimony mineralizations of Jbel Haouanite (Eastern High Atlas, Morocco) are hosted by quartz veins in tectonic structures carried by Ordovico-Silurian Paleozoic formations. At least three phases of folding tectonics affected the area, inducing three generations of folds accompanied by two flow schistosities and a fracture one. Magmatic intrusions of a rhyodacitic nature are post-Silurian and prior to mineralization. From a mineralogical point of view, paragenesis includes native gold, stibnite, valentinite, stibiconite, as well as antimony and lead sulfosalts. Petrographic studies and chemical analyzes show the lack of correlation between gold and the different elements. Thus, the gold would have deposited later to antimony and is associated with oxidation minerals, especially valentinite. The results of the analyzes on different diagrams makes it possible to conclude that the gold mineralizations are of the mesozonal to epizonal orogenic type and they would be late-Hercynian.